Pengaruh Enivironmental Cost terhadap Eko-Efisiensi dengan Environmenta Disclosure sebagai Pemediasi - Novriana, Annisa Ulya; Fakhroni, Zaki (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2022)
This research aims at analyzing influence of environmental cost on the eco-efficiency, environmental cost on the environmental disclosure, environmental disclosure on the eco-efficiency, and environmental disclosure as mediator on influence of environmental cost towards the eco-efficiency. The population of this research were manufacturing and coal-mining companies listed in Bursa Efek Indonesia in the period of 2012-2018. Using a purposive sampling method there were 8 companies as samples and 56 data set were obtained. The data analysis techniques used were, path analysis, and hypothesis test. The results of this research indicate that environmental cost is positively and significantly influence the eco-efficiency, environmental cost positively and significantly influences the environmental disclosure, environmental disclosure positively and significantly influences the eco-efficiency, and environmental disclosure partially mediates the effect of environmental cost on the eco-efficiency.